A Mindfulness-Based Decentering Technique Increases the Cognitive Accessibility of Health and Weight Loss Related Goals - Tapper, Katy; Ahmed, Zoyah (Frontiers in Psychology, 2018)
Previous research has shown that a mindfulness-based decentering technique can help individuals resist eating chocolate over a 5-day period. However, it is unclear how this technique exerts its effect. This study explored one potential mechanism; that decentering increases the cognitive accessibility of relevant goals. Male and female participants (n = 90) spent 5 minutes practicing either a decentering or relaxation (control) technique. They then viewed a picture of a chocolate bar for 3 minutes whilst either applying the decentering technique or letting their mind wander (control). Finally, all participants completed 20 letter strings, rated their motivation for weight loss and for healthy eating, and indicated whether or not they were dieting to lose weight. As predicted, those who had applied the decentering technique produced a greater number of health and weight loss related words when completing the letter strings, compared to those who had simply let their mind wander (p<.001). However, contrary to predictions, these effects were not significantly greater amongst those who were more motivated to lose weight or eat healthily, or amongst those who were dieting to lose weight, though the means were in the predicted directions. The results suggest that this particular mindfulness technique may increase the accessibility of relevant goals. Further research would be needed to (a) compare effects with other strategies that prompt individuals to remember their goals, (b) examine other potential mechanisms of action, and (c) confirm that effects on self-control are mediated by increased goal accessibility.